Electrical properties of polyimide composite films containing TiO2 nanotubes. Issue 11 (14th November 2015) - Olariu, Marius Andrei; Hamciuc, Corneliu; Okrasa, Lidia; Hamciuc, Elena; Dimitrov, Lubomir; Kalvachev, Yuri
Abstract : A study on the dielectric behavior of polyimide composite films containing different amounts of TiO2 nanotubes (TNs) was performed. The films were prepared by casting solutions resulting from direct mixing of a poly(amic acid) and TNs onto glass plates, followed by thermal imidization. The influence of TNs content on the properties of polyimide composites was investigated. AFM and SEM analyses showed good compatibility between the filler and polymer matrix. Dynamic mechanical analysis and broadband dielectric spectroscopy were used to evidence relaxation processes into the films. The electrical properties were evaluated on the basis of dielectric constant and dielectric loss, and their variation with frequency and temperature. At moderate temperature a secondaryβ relaxation was observed while incorporation of TNs decreased the activation energy and facilitated the appearance of an additionalβ 1 process. An α relaxation and a conductivity process were evidenced at higher temperatures. The values of dielectric constant and dissipation factor increased with TNs amount, and the maximum of σ relaxation peak shifted to higher temperatures. POLYM. COMPOS., 38:2584–2593, 2017. © 2015 Society of Plastics Engineers